The Weather Makers: Our Changing Climate and what it means for Life on Earth - Tim F Flannery (Penguin, 2007)
Tim Flannery takes the reader on a journey through history and around the globe as he describes the diversity of the world's ecosystems and reveals how the earth's climate has changed, causing devastating changes in the weather, from hurricanes to heatwaves.